Neonatal Complications in Infants born to Diabetic Mothers - Hussain, Sammar; Ahmed, Zeeshan; Ishaq, Sadia; Zulqurnain, Hafiz; Arshad, Bilal; Shahid, Husnain (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To determine the range and frequency of complications in neonates born to diabetic mothers.Study Design: Cross-sectional study.Place and Duration of Study: Department of Paediatrics, Pak-Emirates Military Hospital Rawalpindi, Pakistan from  Nov 2021 to May 2022.Methodology: We conducted this study on a total of 120neonates born to diabetic mothers. Neonates born to women with metabolic syndrome, polycystic ovarian syndrome, patients taking steroids, history of eclampsia, and patients with a history of heart disease were excluded. All patients were followed up for one month i.e., the neonatal period for the development of complications.Results: Hypoglycaemia was seen in 62(51.67%) of the neonates, while hypocalcaemia affected 72(60.00%) of them. A total of 36(30.00%) of the new borns were born with macrosomia. Moreover, hyperbilirubinaemia affected 41(34.17%), while 30(25.00%), 12(10.00%) and 24(20.00%) neonates had polycythaemia, respiratory distress syndrome and low birth weight, respectively.Conclusion: Neonates born to diabetic mothers are at risk of developing serious, sometimes life-threatening complications, and require constant vigilance to prevent morbidity and mortality.